Design of Decision Support Systems Increase Position with Analytical Methods Hiearrachy Procces (Study Case PT Bintang Timur NGD ) - Arjuna Setiawan Soeksin Putra; Ayuningtyas Ayuningtyas; Tegar Heru Sesilo (Jurnal Sistem Informasi Universitas Dinamika, 2017)
Decision support system of promotion is a system that helps the decision maker in determining the right staff in getting a promotion speed and validation in processing the information is one requirement needed by the support of the decision to be able to minimize the risk it. Analytical Hierarchy Procces (AHP) is one method that is aimed at making information to support the decision of the decision maker.AHP method works by composing a complex problem and multiple criteria into a hierarchy structure, in which each level is filled with a certain element. The method used in this research is the System Development Life Cycle (SDLC).SDLC has a cycle to develop or create a system by starting from one stage to the final stage and back again to the early stages of forming cycles.The results of the study produced is expected to support the decision maker in determining the employee who received a promotion.